Comparison of Cumulative Live Birth Rates Between GnRH-A and PPOS in Low-Prognosis Patients According to POSEIDON Criteria: A Cohort Study - Zhang, Shaodi; Yin, Yisha; Li, Qiuyuan; Zhang, Cuilian (Frontiers in Endocrinology, 2021)
Objective: To compare the cumulative live birth rate (CLBR) of a gonadotropin-releasing hormone (GnRH) antagonist regimen and a progestin-primed ovarian stimulation (PPOS) regimen in low-prognosis patients according to POSEIDON criteria. Design: Single-center, retrospective, observational study. Setting: Henan Provincial People’s Hospital, Zhengzhou, China Patients: Women aged ≤40 years, body mass index <25 kg/m2, who underwent in vitro fertilization (IVF) or intracytoplasmic sperm microinjection (ICSI) and met POSEIDON low-prognosis criteria. Intervention: GnRH or PPOS regimen with IVF or ICSI. Main Outcome Measure: CLBR per oocyte retrieval cycle. Results: Per oocyte retrieval cycle, CLBR was significantly higher with GnRH antagonist versus PPOS (35.3% vs 25.2%; P<0.001). In multivariable logistic regression analysis, CLBR per oocyte retrieval cycle was significantly lower with PPOS versus GnRH antagonist before (OR 0.62 [95% confidence intervals (CI): 0.46, 0.82; P=0.009]) and after (OR 0.66 [95% CI: 0.47, 0.93; P=0.0172]) adjustment for age, body mass index, infertility type, infertility duration, baseline follicle stimulating hormone, anti-Müllerian hormone (AMH), antral follicle count (AFC), and insemination method. CLBR was numerically higher with the GnRH antagonist regimen than with PPOS, across all of the POSEIDON groups, and was significantly higher in patients aged ≥35 years with poor ovarian reserve [AFC <5, AMH <1.2 ng/mL] (unadjusted, P=0.0108; adjusted, P=0.0243). Conclusion: In this single-center, retrospective, cohort study, patients had a higher CLBR with a GnRH antagonist versus PPOS regimen, regardless of other attributes.